The comparison about levels of physical competence a motor performance between students of a public school and students of a private school in Pelotas - Dos Santos, Cibele Alves (2013)
The aim of the study was to compare the levels of physical fitness and motor performance of students at a public schooland a private school in the urban area of Pelotas. The sample was composed of 32 students aged between 13 and 17 years. We used a battery of tests of Project Sport Brazil (BR-PROESP) that gathers and measures somatomotores tests to assess the indicators of body growth, nutritional status, physical fitness related to health and sports performance. In addition, variables were measured skinfold thickness, waist circumference and handgrip strength. Data analysis was performed using Stata, version 10.0 through descriptive analysis (mean and standard deviation) and Student's t-test for unpaired verify the mean differences between groups, using the level of p ≤ 0.05. The main results were around the fat percentage, which was higher for private school for both sexes, girls 30.4% against 16.4% for boys and 21% vs. 13.4%, moreover, waist circumference among girls showed 85.4 cm versus 70.6 cm, in public and private schools respectively, with p = 0.01. We conclude that in motor variables and physical fitness, students showed no significant differences, while for the fat percentage in both sexes and waist circumference among girls the values are significant. Thus, greater attention is needed to the variables of physical fitness and health.